Anti-domain 1 β2 glycoprotein antibodies increase expression of tissue factor on monocytes and activate NK Cells and CD8+ cells in vitro - Manukyan, Gayane; Martirosyan, Anush; Slavik, Ludek; Margaryan, Sona; Ulehlova, Jana; Mikulkova, Zuzana; Hlusi, Antonin; Papajik, Tomas; Kriegova, Eva (Auto- immunity highlights, 2020)
BACKGROUND: β2-Glycoprotein I (β2GPI) represents the major antigenic target for antiphospholipid antibodies (aPL), with domain 1 (D1) being identified as a risk factor for thrombosis and pregnancy complications in APS. We aimed to analyse the ability of aPL, and particularly anti-D1 β2GPI, to stimulate prothrombotic and proinflammatory activity of immune cells in vitro. METHODS: Peripheral blood mononuclear cells (PBMCs) from 11 healthy individuals were incubated with: (1) "anti-D1(+)"-pooled plasma derived from patients suspected of having APS contained anticardiolipin antibodies (aCL), lupus anticoagulant (LA), anti-β2GPI and anti-D1 β2GPI; (2) "anti-D1(-)"-pooled plasma from patients suspected of having APS contained aCL, LA, anti-β2GPI, and negative for anti-D1 β2GPI; (3) "seronegative"-negative for aPL. RESULTS: The presence of anti-D1(+) and anti-D1(-) plasma resulted in increased HLA-DR and CD11b on monocytes. While only anti-D1(+) plasma markedly increased the percentage and median fluorescence intensity (MFI) of CD142 (tissue factor, TF) on monocytes in comparison with those cultured with anti-D1(-) and seronegative plasma. Anti-D1(+) plasma resulted in increased percentage and MFI of activation marker CD69 on NK and T cytotoxic cells. Expression of IgG receptor FcγRIII(CD16) on monocytes and NK cells was down-regulated by the anti-D1(+) plasma. CONCLUSIONS: Taking together, our study shows the ability of patient-derived aPL to induce immune cell activation and TF expression on monocytes. For the first time, we demonstrated the influence of anti-D1 β2GPI on the activation status of monocytes, NK and cytotoxic T cells. Our findings further support a crucial role of D1 epitope in the promotion of thrombosis and obstetrical complications in APS.
Keywords: NK cells; B cells; T cells; Antiphospholipid antibodies; Anti-domain 1 β2GPI; Monocytes; Neutrophils; Plasma pool; Primary immune cells